Effect of thrombin on the fibrinolytic activity of cultured bovine endothelial cells. - Loskutoff, D J (1979)
The vascular endothelium is a rich source of plasminogen activator (PA) and thus of blood vessel-associated fibrinolytic activity. Cultured bovine aortic endothelial cells were employed to determine if components of the coagulation system interact with the endothelium to modify expression of this activity. The addition of thrombin to these cultures led to a rapid decline in intracellular PA activity, with as little as 3 ng/ml, or 0.1 nM thrombin causing a 50% decrease within 30 min. Thrombin inactivated with diisopropylflurophosphate or hirudin did not elicit the response. Although control cultures secreted high levels of PA, no PA activity could be detected in the media surrounding the thrombin-treated cells. This loss of activity did not appear to result from direct inactivation of PA by thrombin. These observations indicate that the fibrinolytic potential of cultured endothelial cells is rapidly suppressed by trace amounts of thrombin. The generation of thrombin at sites of vascular injury may have a similar effect on the endothelium.